Simulating the Tone River eastward diversion project in Japan carried out 4 centuries ago - J. Trošelj; J. Trošelj; N. Hanasaki (Hydrology and Earth System Sciences)
The Tone River is the largest river in Japan, flowing from the Kanto Plain westward to the Pacific Ocean. The river originally flowed southward, entering Tokyo Bay, but the Tone River eastward diversion project (TREDP) in the 17th century and many later projects changed the flow route to that of today. The gradual process of eastward diversion has been extensively studied from the historical viewpoint, revealing that the initial project in the 17th century was principally intended to establish a stable navigation route. However, no scholars have yet proven this hypothesis via hydrological modeling.